Mobile commerce applications - Shi, Nansi, 1953- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2004)
"This book addresses and explores the critical architectural issues in constructing m-commerce applications and in applying mobile technologies in different areas, including methodologies, enabling technologies, models, paradigms, architectures, standards and innovations"--Provided by publisher.